2014
DOI: 10.1159/000357564
|View full text |Cite
|
Sign up to set email alerts
|

Extended First-Trimester Screening Using Multiple Sonographic Markers and Maternal Serum Biochemistry: A Five-Year Prospective Study

Abstract: Objective: To examine the performance of first-trimester screening test combining several fetal sonographic and maternal biochemical markers for major aneuploidy in a Chinese population. Methods: This was a prospective study performed over 5 years between January 2005 and December 2010 in Taiwan, with 20,586 cases that had a combination of a variety of sonographic markers and maternal serological β-human chorionic gonadotropin and pregnancy-associated plasma protein-A levels assessed at first trimester screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…However, we failed to reach the excellent 100% detection rates obtained by Hsiao et al [14] or Ghaffari et al [15] at lower FPRs of 2.4% or 3.4%, respectively.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, we failed to reach the excellent 100% detection rates obtained by Hsiao et al [14] or Ghaffari et al [15] at lower FPRs of 2.4% or 3.4%, respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…Using an ultrasound only based protocol, with NT and all additional markers, for a FPR of 5%, the detection rate for T21 reached 94-97.5% [11][12][13]. When all of these markers were added to a traditional combined test, the detection rate substantially increased to up to 100%, for a FPR of 2.4% [14] or 3.4% [15].…”
Section: Www Journalsviamedicapl/ginekologia_polskamentioning
confidence: 99%
“…For the same cutoff, the detection rate for trisomy 18, 13, triploidy, and Turner syndrome was 96% [17]. Other study groups have found similar results [18][19][20].…”
Section: Comparison With Previous Studiesmentioning
confidence: 52%
“…Eight performed the test of NT alone, including 103 568 patients. Most of the studies (8/24) chose the cut‐off value of 1 in 300 as the positive result, six studies chose the cut‐off value of 1 in 250, three studies were 1 in 270, one was 2.5 mm, one was 95 th centile, one was 99 th centile and one used 1.5 MoM (multiples of the calculated regressed median), respectively. Most of the studies (21/24) were published in English, and the remaining three articles were published in Chinese.…”
Section: Resultsmentioning
confidence: 99%